Upaya Perpustakaan Dalam Meningkatkan Minat Baca Siswa Sekolah Dasar Unggulan Aisyiah Taman Harapan Curup - Rhoni Rodin; Riska Putri; Seli Novita; Soliha Nisa Ul Jannah; Genta Putri Roliansy (THE LIGHT : Journal of Librarianship and Information Science, 2024)
This study aims to evaluate the efforts of the library in increasing students' reading interest at Aisyiah Taman Harapan Curup Elementary School. The research analyzes various strategies implemented by the library to facilitate and develop reading habits among students. The findings show that students have a very high interest in reading, which is influenced by regular teaching activities in the library managed by teachers and librarians. These activities include three scheduled library visits each day, allowing students to consistently engage in reading. Specific efforts include book analysis competitions with prizes to motivate students and collaboration with the local library to expand access to various book collections. However, the study also identifies the need for reorganizing the library space and updating the service system to enhance comfort and accessibility for users. Organizing books by category is also recommended to make searching easier. These findings provide valuable insights into the effectiveness of library methods in promoting reading interest and offer recommendations for further development